Analysis of Fiqh Muamalah and Positive Law on Auction Transactions on Instagram - Waru, Putra Warna; Idzhar, Muhammad (Ghaly: Journal of Islamic Economic Law, 2024)
The development of technology 4.0 in today's society is growing rapidly. Until finally business actors and consumers in auction buying and selling transactions are very easy and no longer face to face in offering and selling a product to consumers. This is influenced by the shift in people's lifestyles that utilize technology in buying and selling auctions on one of the intagram social media. This research will analyze first how the practice of auctioning on Instagram, second how the analysis of fiqh muamalah and positive law on auction transactions on Instagram. The method used in this research is the Normative Law method, with the approach (Comparative Approch), in collecting data this research uses (Library search) and instagram posts, and there are data processing techniques namely editing, systematic and description and data analysis techniques used are qualitative analysis for presentation done descriptively. The results of this study indicate that, first, the practice of organizing buying and selling auctions on Instagram is not much different from the practice of organizing organized by the auction hall Second, the organization of buying and selling auctions on Instagram in the view of fiqh muamalah is permissible. It is different with positive law that the organization of the practice of buying and selling auctions on Instagram is said to be illegal and is a form of illegal action.